Once upon a duke ebook 12 dukes of christmas, #1. - Ridley, Erica (12 Dukes of Christmas, 2018)
Beware romantic spirits from Christmas past... Due to the terms of an estranged relative's will, the Duke of Silkridge must revisit the cold, unforgiving mountains where he lost everything he once loved. As soon as he restores his family legacy, he'll return to London where he belongs. He definitely won't rekindle the forbidden spark crackling between him and the irresistible spitfire he'd left behind... Noelle Pratchett is immune to charming scoundrels like the arrogant duke. He stole her heart, stole a kiss, and then stole away one night never to return. Now he's back—and they both know he won't stay. But how can she maintain her icy shields when every heated glance melts her to her core? The 12 Dukes of Christmas is a series of heartwarming Regency romps nestled in a picturesque snow-covered village. After all, nothing heats up a winter night quite like finding oneself in the arms of a duke!